(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The police and their roles are very significant in the area of criminology. Since it is the primary responsibility of the police to apprehend and execute suspects before the end of the crime reduction court. The police are constitutionally allowed to use intimidation another types of violence to uphold civil and societal security. The simple understanding of crime criminology is a necessity for the police, so that’s why nearly every nation in the world has a police criminology branch. So the officers are qualified professionally with the experience of criminology. This is clear that credible, committed and efficient police department will guarantee a safe and prosperous community. While it is not necessary for the police to eradicate violence entirely from culture, it may be regulated and managed at a sufficient level. Alternatively, difficult, incompetent, unlettered, and fake police services will render the offenders suited to make the lives of the general population unbearable. This study confirms the role of the police in the criminal justice system.